Crosstalk between fatty acid metabolism and tumour-associated macrophages in cancer progression - Zaidi, Noorzaileen Eileena; Shazali, Nur Aima Hafiza; Thean, Chor Leow; Osman, Mohd Azuraidi; Ibrahim, Kamariah; Nik Abd Rahman, Nik Mohd Afizan (China Medical University, 2022)
Over the last few decades, cancer has been regarded as an independent and selfsustaining progression. The earliest hallmarks of cancer comprise of sustaining proliferative signalling, avoiding growth suppressors, resisting cell death, enabling replicative immortality, inducing angiogenesis, and activating invasion and metastasis. Nonetheless, two emerging hallmarks are being described: aberrant metabolic pathways and evasion of immune destruction. Changes in tumour cell metabolism are not restricted to tumour cells alone; the products of the altered metabolism have a direct impact on the activity of immune cells inside the tumour microenvironment, particularly tumour-associated macrophages (TAMs). The complicated process of cancer growth is orchestrated by metabolic changes dictating the tight mutual connection between these cells. Here, we discuss approaches to exploit the interaction of cancer cells' abnormal metabolic activity and TAMs. We also describe ways to exploit it by reprogramming fatty acid metabolism via TAMs